Anemia e deﬁciência de ferro na insuﬁciência cardíaca - Gil, VM (2015)
Heart failure is a common problem and a major cause of mortality, morbidity and impaired quality of life. Anemia is a frequent comorbidity in heart failure and further worsens prognosis and disability. Regardless of anemia status, iron deficiency is a common and usually unidentified problem in patients with heart failure. This article reviews the mechanisms, impact on outcomes and treatment of anemia and iron deficiency in patients with heart failure.